Risk Factors for Diabetic Retinopathy - Naufallah Dinda Harumi; Ramzi Amin (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2020)
Introduction. Diabetic retinopathy is a progressive microangiopathy characterized by damage and occlusion of small blood vessels. The earliest pathologic changes are thickening of the capillary endothelial basement membrane and a reduction in the number of pericits. Diabetic retinopathy is the main cause of vision loss in type 1 of DM patients and has various risk factors such as chronic hyperglycemia, hypertension, hypercholesterolemia, and elevated HbA1C levels. Methods. This research was conducted using a descriptive observational analytic method with a cross sectional approach at The Eye Polyclinic Dr. Mohammad Hoesin General Hospital Palembang used secondary data on diabetic retinopathy patients. The sample consisted of 64 patients with a total sampling technique, there were 50 patients who met the inclusion criteria. Results. There was a significant relationship between HbA1C levels (p value = 0.050) with a PR value = 1.463 and total cholesterol (p value = 0.038) with a PR value = 1.667 for diabetic retinopathy. Conclusion. HbA1C levels and total cholesterol are significant risk factors for diabetic retinopathy.